Shirley Valentine [videorecording (DVD)] - Collins, Pauline, 1940-; Conti, Tom (Archive collection., 2013)
Pauline Collins is the hilariously endearing Shirley Valentine, wisecracking, completely unpredictable English housewife who proves it's never too late to recapture your dreams. Bored with her suburban life, Shirley takes a chance on adventure when a friend invites her on a vacation to Greece. Within no time, she's back to her rebellious teenage roots, saying yes to a wild fling with a handsome rogue (Tom Conti) and the life she's always wanted.